Relie qingzhu Zhongguo gonghui dijiuci quanguo daibiao dahui shengli zhaokai - Chao Deren,
'Enthusiastically celebrate the victorious convening of the ninth meeting of national representatives of the All-China Federation of Trade Unions.' Printno. 8027.6194.